2003
DOI: 10.1161/01.res.0000100367.45446.a3
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Depletion Impairs Vascular Reactivity to Endothelin-1 by Reducing Store-Operated Ca 2+ Entry Dependent on TRPC1

Abstract: Abstract-The reactivity of the vascular wall to endothelin-1 (ET-1) is influenced by cholesterol, which is of possible importance for the progression of atherosclerosis. To elucidate signaling steps affected, the cholesterol acceptor methyl-␤-cyclodextrin (m␤cd, 10 mmol/L) was used to manipulate membrane cholesterol and disrupt caveolae in intact rat arteries. In endothelium-denuded caudal artery, contractile responsiveness to 10 nmol/L ET-1 (mediated by the ET A receptor) was reduced by m␤cd and increased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
178
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(187 citation statements)
references
References 32 publications
7
178
2
Order By: Relevance
“…It was reported that PD98059 (5 Â 10 À5 mol/L) and MbCD (10 À2 mol/L) did not produce toxic effects on cells but inhibited them. 14,15 Furthermore, both agents inhibited Ang II-induced GMC proliferation, suggesting that p-ERK1/2 and caveolin-1 were involved in regulating Ang II-induced GMC proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…It was reported that PD98059 (5 Â 10 À5 mol/L) and MbCD (10 À2 mol/L) did not produce toxic effects on cells but inhibited them. 14,15 Furthermore, both agents inhibited Ang II-induced GMC proliferation, suggesting that p-ERK1/2 and caveolin-1 were involved in regulating Ang II-induced GMC proliferation.…”
Section: Discussionmentioning
confidence: 95%
“…In rat aorta, antisense inhibition of TRPC6 also markedly inhibited the ␣ 1 -adrenoreceptor-mediated increase in [Ca 2ϩ ] cyt (53). Therefore, which TRPC isoform(s) form ROC or SOC may depend on (i) cell type (e.g., TRPC6 may be involved in forming SOC in PASMC, but ROC in aortic smooth muscle cells), (ii) composition (or ratio) of different TRP subunits in the heterotetram (e.g., a channel made up of one TRPC3 and three TRPC6 may be a ROC and a channel made of one TRPC1, two TRPC3, and one TRPC6 may be a SOC), (iii) heteromultimeric assembly of functional channels (e.g., a ROC-TRPC6 may form heterologous SOC with SOC-TRPCs like TRPC3 and TRPC7) (44,45,47,48,51,52), and (iv) localization or compartmentalization (e.g., ligand-receptor interaction and store depletion can activate a TRPC1-dominant channel in caveolae) (30). In addition, human TRP genes often show tissue-specific expression patterns and likely encode both ROC and SOC (29).…”
Section: Discussionmentioning
confidence: 99%
“…A central aspect of pulmonary vascular remodeling is medial hypertrophy caused by sustained pulmonary vasoconstriction (2-4), excessive pulmonary artery smooth muscle cell (PASMC) proliferation (5), and inhibited PASMC apoptosis (6, 7), resulting in a narrowed vascular lumen and increased PVR. Although its etiology remains unclear, elevated levels of circulating mitogens, dysfunction or down-regulation of receptors and ion channels, upregulation of transporters, and heightened activity of elastases and glycoproteins have been implicated in IPAH (5,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Transient receptor potential (TRP) channel genes may encode subunits that form receptor-(ROC) and store-(SOC) operated Ca 2ϩ channels in many cell types, including PASMC and pulmonary artery endothelial cells (PAEC) (28,(30)(31)(32)(33)(34). Ca 2ϩ entry through ROC and SOC increases [Ca 2ϩ ] cyt , allowing for phosphorylation of signal transduction proteins and transcription factors (23,24,(35)(36)(37)(38), that are essential for the progression of the cell cycle (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In smooth muscle and endothelial cells, caveolae are important sites for membrane receptors and channels to associate closely with the endo-plasmic/ sarcoplasmic reticulum [12] and for ligand-mediated Ca 2+ entry through ROC and SOC [13][14][15]. Intracellular messenger pathways regulated by cAMP and Ca 2+ are tightly integrated and functionally colocal-ized in caveolae [16,17].…”
mentioning
confidence: 99%